Validation of the Student Athletes’ Motivation Toward Sports and Academics Questionnaire (SAMSAQ) for Korean College Student-Athletes: An Application of Exploratory Structural Equation Modeling - Lee, Youngjik; Immekus, Jason; Lim, Dayoun; Hums, Mary; Greenwell, Chris; Cocco, Adam; Kang, Minuk (Frontiers in Psychology, 2022)
The purpose of this study was to validate the Korean version of the SAMSAQ using exploratory structural equation modeling (ESEM). A total of 412 (males 77%; females 23%) South Korean collegiate student-athletes competing in 27 types of sports from 13 different public and private universities across South Korea were analyzed for this study. ESEM statistical approach was employed to examine psychometric properties of SAMSAQ-KR. To obtain content validity, the SAMSAQ-KR was inspected by a panel of content subject experts. Athletic Identity Measurement Scale (AIMS) was used to obtain convergent validity. The results of this study illustrated that the SAMSAQ-KR appears to be a robust and reliable instrument.